2018
DOI: 10.1186/s12888-018-1904-7
|View full text |Cite
|
Sign up to set email alerts
|

Demographic, psychosocial and clinical factors associated with postpartum depression in Kenyan women

Abstract: BackgroundFew longitudinal studies have examined associations between risk factors during pregnancy and mental health outcomes during the postpartum period. We used a cohort study design to estimate the prevalence, incidence and correlates of significant postpartum depressive symptoms in Kenyan women.MethodsWe recruited adult women residing in an urban, resource-poor setting and attending maternal and child health clinics in two public hospitals in Nairobi, Kenya. A translated Kiswahili Edinburgh Postpartum De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
56
3
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 52 publications
7
56
3
5
Order By: Relevance
“…Depression Research and Treatment surveys [22,[26][27][28][29][30][31]. Research in both urban and rural areas of South Africa has shown that the EPDS is a validated screening instrument [32][33][34][35][36], whereas other sub-Saharan countries have also validated the EPDS to screen for depression during and after pregnancy [19,[32][33][34][35].…”
Section: Measurement Instrument the Edinburgh Postnatalmentioning
confidence: 99%
“…Depression Research and Treatment surveys [22,[26][27][28][29][30][31]. Research in both urban and rural areas of South Africa has shown that the EPDS is a validated screening instrument [32][33][34][35][36], whereas other sub-Saharan countries have also validated the EPDS to screen for depression during and after pregnancy [19,[32][33][34][35].…”
Section: Measurement Instrument the Edinburgh Postnatalmentioning
confidence: 99%
“…Although extensive studies have been conducted on postpartum depression [24][25][26][27][28][29], few have focused on women who have experienced a perinatal death [14,[30][31][32]. In our study context, the association between perinatal death and postpartum depression has not been established making this evidence scarce in Northern Uganda.…”
Section: Introductionmentioning
confidence: 97%
“…In the presented study, the support received from relatives and midwives during childbirth was not an indicator of postpartum depression in women. Other studies report that the likelihood of PPD has increased more than seven-fold if there was conflict with a partner, including serious economic problems and ending the relationship [4,35]. Ongeri et al [35] report that mothers who had a good relationship with their mother-in--law and partner who assisted in raising the child, were less likely to have PPD.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies report that the likelihood of PPD has increased more than seven-fold if there was conflict with a partner, including serious economic problems and ending the relationship [4,35]. Ongeri et al [35] report that mothers who had a good relationship with their mother-in--law and partner who assisted in raising the child, were less likely to have PPD. Scientific literature provides significant relationships between prenatal stressful life events and the risk of postpartum depression in women.…”
Section: Discussionmentioning
confidence: 99%